Tax Incentives, Tax Enforcement, and Enterprise R&D Investment: Evidence From Chinese A-Share Listed - Sun, Ying (Frontiers in Psychology, 2022)
This study investigates the relationship between tax incentives, tax enforcement, and R&D investment in Chinese enterprises. Tax compliance is an important part of organizational behavioral psychology, which will impact organizational innovation activities. Therefore, the present study utilizes the panel data of Chinese A-share listed companies collected from the China Stock Market & Accounting Research (CSMAR) database from 2011 to 2020 to conduct empirical research. It tests the policy effect of tax incentives on enterprise R&D investment and examines the impact of tax enforcement on enterprise R&D behavior and its moderating effect on the relationship between tax incentives and enterprise R&D investment. The results show that China's preferential tax policies positively affect enterprise innovation activities, and stable and continuous tax incentives can stimulate enterprises to increase R&D investment. Increasing the intensity of tax enforcement has a significant positive impact on enterprise R&D investment, which means that the promotion effect of "governance effect" and "incentive effect" caused by tax enforcement may exceed the negative impact brought by its "taxation effect" and "rent-seeking effect." The study suggests that with the strengthening of tax enforcement, the promotion effect of tax incentives is weakened, which is only reflected in non-state-owned enterprises. Finally, we propose relevant policy recommendations based on the research results. This includes further optimizing the collocation of tax types and preferential methods, encouraging enterprises to face up to the role of tax enforcement as an external governance mechanism, and promoting the tax department to standardize the enforcement process and taxation services. The paper presents a range of theoretical and practical implications for both firm managers and policymakers.